Chemopreventive Properties Curcuma heyneana Rhizome Ethanolic Extract on Hepatocellular Carcinoma Cells, JHH-4 - Santoso, Christopher Filando; Rahmawati, Desty Restia; Nugraheni, Nadzifa; Adisusilo, Midori Rahmadhany Putri; Maharani, Dini; Hermawan, Adam; Meiyanto, Edy (Indonesian Journal of Cancer Chemoprevention, 2024)
Hepatocellular carcinoma is the most common type of liver cancer. Curcuminoids are natural polyphenol compounds abundant in Curcuma heyneana ethanolic extract (CHE) and are known to inhibit breast and cervical cancer cell proliferation. Based on previous research, curcuminoid compounds have been studied to inhibit the growth of the liver cancer cell model, HepG2. This study aims to examine the potential of CHE as a chemopreventive agent in liver cancer using JHH-4 cell as a model. CHE was obtained by maceration method using ethanol which was then identified for its phytochemical profile using thin layer chromatography (TLC). Then TLC results were quantified to calculate the levels of compounds present in the CHE based on spot intensity with ImageJ software. 2,2-Diphenyl-1-picrylhydrazyl (DPPH) antioxidant assay was conducted to determine the radical scavenging activity of CHE. Cytotoxic activity of CHE on JHH-4 liver cancer cells was tested by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. Extraction produces a yield of 10.2 %w/w. CHE contains 4.52 %w/w curcuminoid compound consisting of 0.49 %w/w curcumin, 3.21 %w/w demethoxycurcumin, and 0.82% w/w bisdemethoxycurcumin. CHE exhibited antioxidant activity with an IC50 value of 378.96 μg/mL, meanwhile ascorbic acid as a positive control has an IC50 value of 8.49 μg/mL. Cytotoxic activity of CHE on JHH-4 cells is characterized by an IC50 value of 16.62 μg/mL which is classified as having strong cytotoxic activity. This study concluded that CHE has the potential to be developed as a chemopreventive agent in liver cancer.Keywords: liver cancer, hepatocelullar carcinoma, Chemopreventive, antioxidant,Curcuma heyneana.